Pengaruh Penambahan Sukrosa terhadap Kualitas Susu Bubuk Kambing Peranakan Ettawa (PE) - Dwi Septi Fatinah; Roisu Eny Mudawaroch; Rinawidiastuti Rinawidiastuti (Universitas Muhammadiyah Purworejo, 2022)
The aim of the study was to determine the effect of the addition of sucrose at different levels on the quality of Ettawa crossbreed (PE) goat milk powder. The research was conducted at the Integrated Animal Husbandry Laboratory, University of Muhammmadiyah Purworejo and the Che-mix Laboratory Yogyakarta. The treatment given was sucrose with levels of 0% (SB0), 10% (SB1), 20% (SB2), 30% (SB3) and 40% (SB4). The method used a completely randomized design (CRD) with 5 treatments and 20 panelists as replicates. The parameters taken were water content, protein content, fat content, total sugar content and organoleptic tests which included color, taste, aroma and texture. The results showed that the addition of sucrose had an effect on decreasing the water content, protein content, fat content and increasing the total sugar content of powdered milk. The results of the anova analysis of the organoleptic test showed that the addition of sucrose had a significant effect (P<0.05) on the quality of color, taste, aroma and texture of powdered milk. Based on the results of the study, it can be concluded that the addition of 0% to 40% sucrose level significantly affected the decrease in water, protein, fat content and increased total sugar content. The organoleptic test with the best treatment was SB1.